The Effect Of Acalypha Indica Linn (Anting Anting Leaves) On Staphylococcus Aureus Causes Pioderma - Annisa Nur Azhari Hidayati Bujan; Sri Vitayani M; Andi Miranti (Sean Institute, 2024)
Indonesia is a country rich with various types of plants that have medicinal properties, both from the types of fruits, vegetables, spices, food crops and plants that grow wild around us. Acalypha indica (L) is a family of Euphorbiaceae, is an annual plant and is commonly found in gardens, roadsides, rubbish bins, fields throughout the plains of India. The method used is literature review with Narrative Review design. The results obtained in this literature are that there are 7 articles obtained with restrictions from 2017 - 2023 and an in-depth analysis of the strengths and limitations of each article on the effects of acalypha indica I. (earring leaf) on staphylococcus aureus that causes pyoderma., 7 articles discussing acalypha indica I (earring leaves) against staphylococcus aureus that causes pyoderma, 1 article mentions that acalypha indica I (earring leaves) is formulated in antibacterial ointment preparations (journal 4), Furthermore, the author identified 1 article that discusses the ethanol extract of earring leaves with concentrations of 5 grams, 10 grams and 15 grams showing the results of the inhibition zone on Stapylococcus aureus bacteria (journal 1). There is 1 article that discusses earring root extract has weak antibacterial activity against S. aureus and MRSA with MIC values of 50 and 100 mg/mL. (Journal 2). Based on the results of the identification and review of several in this literature review, it can be concluded that there is an effect of acalypha indica I. (earring leaf) against staphylococcus aureus that causes pyoderma. Staphylococcus aureus is one of the bacteria that most often infects humans. Plants that have potential as antibacterials are earring plants